Community capacity building: a review of its implication in tourism development - Aref, Fariborz; Redzuan, Ma'rof; Gill, Sarjit S. (Marsland Press, 2010)
The purpose of this study is to explore the concept of community capacity building and implication of its dimensions in tourism development processes. Community capacity building is a necessary condition for improving the process of tourism and enhancing its benefits for local communities. Therefore, assessing dimensions of community capacity building is an important step in developing strategies to achieve community goals. This study also provided unique theoretical framework for tourism developers and researchers for tourism development in local communities with respect to building community capacity.